Radiation Safety Evaluation: Leakage and Dose Rate Distribution of a Laboratory X-Ray System - Firmansyah, Anugrah (Schrödinger: Journal of Physics Education, 2026)
Purpose of the study: This study aims to measure and analyze potential radiation leakage and dose rate distribution around the Phywe X-ray unit in an educational physics laboratory using a survey meter, in order to evaluate safety conditions and support improved radiation protection for users. Methodology: This study employed a PHYWE X-ray Unit, survey meter (Geiger-Müller type), tape measure (Stanley 5 m), and digital stopwatch (Casio HS-3V). The method included literature review, experimental multi-point radiation leak measurement, repeated exposure timing, and dose rate mapping. Data were processed using Microsoft Excel for tabulation and graphical analysis. Main Findings: Radiation intensity was 0 µSv/h at most measurement points. Detectable values occurred at 200 cm (261.12 µSv/h) and 300 cm (67.32 µSv/h), showing decreasing intensity with increasing distance. Dose rates were 36.72 µSv/h at 150 cm and 276.42 µSv/h at 650 cm. Results indicate dominant low exposure levels with variations influenced by distance, scattering, shielding, and measurement geometry. Novelty/Originality of this study: This study provides systematic multi-point radiation leakage mapping of an educational-scale Phywe X-ray unit in a non-clinical laboratory setting. It generates empirical dose distribution data rarely reported for teaching laboratories, verifies inverse square behavior under real conditions, and reveals deviations caused by scattering and shielding, thereby advancing practical radiation safety knowledge beyond clinical-focused studies.